Paraneoplastic neurologic syndrome: A practical approach - Kannoth, Sudheeran (Medknow Publications & Media Pvt Ltd, 2012)
Paraneoplastic neurological syndromes (PNS) are rare disorders associated with cancer, not caused by direct invasion, metastasis or consequences of treatment. They are usually autoimmune in nature. Often, PNS precedes the manifestations of cancer. Onconeural antibodies are important in the diagnosis and management of these disorders. These antibodies are specific for the malignancy rather than for a particular neurological syndrome. Often, there are different antibodies associated with the same syndrome. Multiple antibodies are also known to coexist in a given patient with malignancy. While investigating a patient for suspected PNS, the entire gamut of onconeural antibodies should be investigated so as not to miss the diagnosis. In 30–40% of the cases, PNS can occur without antibodies. Investigations for identifying the underlying cancer can be directed by the antibody panel. If conventional screening for cancer is negative, a positron emission scanning/computed tomography scan can be useful. Patients need follow-up surveillance for cancer if not detected in the first instance. Cancer detection and treatment, immunotherapy and supportive care are important components of treatment of PNS. Immunotherapy is very effective in PNS associated with cell membrane-associated antibodies like voltage-gated potassium channel complex, NMDA receptor antibodies and voltage-gated calcium channel antibodies. Immunotherapy includes steroids, IVIgG, plasmaphereis, cytotoxic medications and rituximab. Supportive therapy includes symptomatic treatment with antiepileptic and analgesic medications, physiotherapy, speech therapy and occupational therapy. PNS can mimic any neurologic syndrome. A high index of clinical suspicion is important for early diagnosis and prompt management and better outcome.